Next-generation fluorescent nucleic acids probes for microscopic analysis of intracellular nucleic acids - Akimitsu Okamoto (Applied Microscopy, 2019)
Abstract Fluorescence imaging of nucleic acids is a very important technique necessary to understand gene expression and the resulting changes in cell function. This mini-review focuses on sequence-specific fluorescence imaging of intracellular RNA and methylated DNA using fluorescent nucleic acid probes. A couple of functional fluorescent nucleic acid probes developed by our laboratory are introduced and the examples of their application to fluorescence imaging of intracellular nucleic acids are described.